Current understanding of chemical degradation mechanisms of perfluorosulfonic acid membranes and their mitigation strategies: a review - Zatoń, M.; Rozière, J.; Jones, D. J. (Sustainable energy & fuels, 2017)
This article provides a comprehensive and up-to-date perspective of the understanding of perfluorosulfonic acid (PFSA) fuel cell membrane degradation phenomena, reviews key concepts for the mitigation of membrane degradation, appraises the effectiveness of these strategies by discussing their benefits and drawbacks, and identifies remaining challenges and research priorities for fuel cell membranes with increased longevity. Identification of stressors and improved understanding of how scavenging reactions proceed are essential for accelerated development of new fuel cell membrane materials with antioxidant properties and enhanced durability. Fuel cells convert the chemical energy of a fuel such as hydrogen into electricity and heat and have the potential to deliver environmental and economic benefits across various sectors, including transportation, power generation, industrial equipment, military power, and consumer electronics. The development of Proton Exchange Membrane Fuel Cell (PEMFC) membranes with increased durability is of crucial importance since it directly impacts fuel cell system lifetime and, therefore, large scale implementation of fuel cell technology. The PFSA proton conducting polymer (ionomer) at the heart of the membrane electrode assembly of a PEMFC is subject to chemical degradation as a result of the attack on the polymer chains by reactive oxygen species generated electrochemically in the fuel cell. For the first time, this article reviews the literature both on mechanisms by which this chemical degradation of the ionomer membrane occurs and the sites on the polymer susceptible to free radical attack, as well as how this learning and increased understanding have been used to build and develop successful mitigation strategies designed to annihilate the harmful effect of oxidative species on membrane integrity.